From fragmented to unified: redefining eco-innovation for interdisciplinary climate solutions - El Ouardi, Boutayna; Boungab, Souad (Frontiers in Sustainability, 2025)
Background and significanceThe concept of eco-innovation has become more significant as businesses are under increasing pressure to lessen environmental issues while preserving their competitive performance. The field has ongoing definitional fragmentation that hinders both theoretical development and practical implication, despite substantial research spanning almost three decades. Current definitions reveal operational ambiguity that offers little direction for organizational action, theoretical fragmentation across fields, and terminological misunderstanding with related concepts.ObjectivesThis study aims to: (1) perform a thorough, systematic review of definitions of eco-innovation from 1996 to 2024; (2) use linguistic analysis to examine theoretical foundations and definitional patterns; (3) identify significant gaps in current conceptualizations; and (4) suggest a unified, theoretically based definition that combines established innovation theories with useful implementation guidance.MethodologyIn accordance with PRISMA guidelines, we used thorough search terms to conduct a systematic search across six databases: Scopus, Web of Science, ScienceDirect, JSTOR, EBSCO, and Google Scholar. By using stringent methods and inter-rater reliability evaluation (Cohen’s Kappa>0.89), 85 identified papers satisfied the inclusion criteria. Data extraction used standardized forms that covered topics as implementation issues, theoretical frameworks, publication details, and precise definitions. The analysis integrated action verb categorization, theme analysis, temporal evolution mapping, and theoretical framework classification.Key resultsFour theoretical foundations are identified: innovation systems (16%), stakeholder theory (24%), institutional theory (28%), and resource-based view (32%). Action verb analysis identifies “develop” as most frequent (67%) with very high implementation clarity, while outcome analysis shows environmental objectives dominate (89%) with strong business focus (67%) but limited social integration (34%). Three definitional types with different theoretical emphasis and practical constraints were identified: output-focused (42%), process-focused (31%), and system-focused (27%).ImplicationsAccording to the unified redefinition, eco-innovation is an organizational capability that comprises four action orientations (adopt, integrate, improve, and develop) and three different forms of innovation (management systems, outputs, and markets). Eco-oriented culture and capabilities facilitate these innovations. This approach offers useful implementation guidance along with theoretical integration that addresses disciplinary fragmentation. The new “eco-oriented capabilities” concept serves as a theoretical link between theories. It facilitates capability development planning and practical strategic focus.